Phylogenetic studies of Phoma species by maximum likelihood analysis - Irinyi, László; Kövics, György; Sándor, Erzsébet (Acta Agraria Debreceniensis, 2008)
The cosmopolitan Phoma genus contains mainly phytopathogenic, opportunistic parasite, and saprophyte fungal species. Up to now the characterization of Phoma species and other taxa of Phoma has so far been determined on the basis of morphology on standardized media, and gene sequence analysis was only used as a confirmative or distinctive complement. In this study we have tried to study phylogenetic relationships by maximum likelihood method in the Phoma genus. We employed a part of the gene responsible for the synthesis of translation elongation factor 1 subunit alpha protein (tef1) containing both introns and exons, a part of the gene responsible for synthesis of tubulin protein and ITS region containing the internal transcribed spacer regions 1 and 2 and the 5.8S rDNA as potential genetic markers to infer phylogenetic relationships among different Phoma taxa. Twenty-four isolates of eleven different Phoma species were firstly characterised by morphologically, and then their tef1, tubulin and ITS sequences were sequenced and analysed by maximum likelihood method carried out by PAUP*4.0b program. According to constructed phylogenetic trees, the different Phoma taxons are well separated. However these trees do not support the traditional Phoma sections based on morphological characterization. The maximum likelihood analyses of all three sequences confirmed that the Phyllosticta sojicola species is clustered with the Phoma exigua var. exigua group and the Phoma sojicola is grouped with Phoma pinodella group. The experienced molecular evidences initiate the demand of reclassification of formerly mentioned soybean pathogens.